Evaluasi Persepsi Pengguna Jalan terhadap Keselamatan Berkendara pada Simpang Tak Bersinyal di Kota Meulaboh - Erliana, Hilma; Novriza, Ferdiansyah; Sari, Nina Novita; Wulansari, Intan (Universitas Teuku Umar, 2025)
Traffic accidents at unsignalled intersections remain a serious problem in Indonesia, particularly in urban areas such as Meulaboh City, West Aceh. The high accident rate at these locations is due to the complexity of road user interactions and inadequate safety facilities. This study aims to analyse road users' perceptions of driving safety at unsignalised intersections, focusing on eight key aspects: demographic characteristics, infrastructure, driving behaviour, accessibility, road physical conditions, social factors, environmental factors, and regulations and enforcement. The research method employed a descriptive quantitative approach, with data collected through a Likert scale questionnaire (1-5) administered to 100 respondents selected via purposive sampling. Data were analysed using a percentage index formula to measure the level of agreement among respondents. The research results show that infrastructure (83,05%) and driving behaviour (83.10%) achieved the highest scores, indicating strong agreement on the importance of improving physical facilities and road user discipline. Meanwhile, road physical condition (75.4%) recorded the lowest score, highlighting the need to improve road surface conditions and drainage. Other findings revealed the significant influence of environmental factors (81.55%) and regulations (81.35%), as well as the role of social awareness (77.3%) and demographics (76.85%). The conclusion of this study emphasises that infrastructure improvements and increased driving discipline need to be prioritised in traffic safety strategies. Data-driven policy support involving public education, law enforcement, and inter-agency collaboration is essential to create a safe, inclusive, and sustainable traffic environment at unsignalised intersections. Concrete recommendations include installing traffic signs/lighting, safety campaigns, and the use of technology.